Assumption of heparin-induced thrombocytopenia in mucopolysaccharidoses - Liliya Aleksandrovna Osipova; Lyudmila Mikhailovna Kuzenkova (Journal of Ideas in Health, 2021)
Background: Mucopolysaccharidoses (MPSs) are a group of lysosomal storage diseases, resulted from glycosaminoglycans’ breakdown failure (GAGs). The study aims to determine the presence of thrombocytopenia, its prevalence, clinical implication, and correlation with the types of MPSs and with the types of glycosaminoglycans storage.